Умови ефективності професійної діяльності вчителів у США - Леврінц Маріанна; Lőrincz Marianna; Levrints Marianna (Візаві, 2019)
Резюме. Метою статті є розкриття умов ефективності професійної діяльності вчителів і чинників, які впливають на якість праці педагогів у США. З’ясовано, що ефективність професійної діяльності вчителя є комплексним утворенням, що поєднує особистісну, діяльнісну і результативну площини, які зумовлюються контекстуальними показниками. Проаналізовано чинники, які впливають на ефективність педагогічної праці та висвітлено заходи її оптимізації: імплементація стандартно-базованої документації, розроблення системи підзвітності, розроблення методів оцінювання ефективності педагогічної діяльності та ін.

Abstract. The purpose of this study is to identify underlying conditions of effective teaching, as well as perceived determiners influencing the quality of teachers’ work in the American educational discourse. To this end, the work applies the following research methods: the interpretative-analytical method aimed at investigating current research trends and pertinent pedagogical conceptualizations of the concept of effective teaching, complemented by synthesis of the available research propositions. Considerable proliferation of theoretical and empirical research in the field of teaching quality both worldwide and in the USA is attributed to teachers’ exceptional role undergirding the final outcomes of any endeavours at improving education, be it students’ learning gains or educational reforms. In conceptualizing and defining the concept of teacher effectiveness three verticals serve as a starting point, termed by the author of this study as individual, activity-related and resultative. The individual vertical embraces teachers’ professional knowledge and skills, personal traits, motivation, professional qualities, educational background and teaching competence. The activity-related vertical pertains to the enactment of the aforementioned elements of the individual vertical in the instructional process and their correlation with student learning. The resultative vertical concerns teachers’ influence on the students’ learning outcomes. It is the primary point for consideration in teacher effectiveness measurements, although, the first two verticals are also included in some evaluation methods. The quality of teaching and its perceived effectiveness is determined by the influence of multifarious factors, the main being teachers’ characteristics, relevant educational background and teaching experience, professional development, socio-cultural contexts in which teachers work, students’ academic results and practices adopted for evaluation purposes. In an effort to improve the quality of teaching, the American educational community has sought and is undertaking empirically supported feasible measures. Among the many important attempts are the implementation of standards of teacher preparation and development, accountability measures (teacher licensing, certification), optimizing models of teacher education and seeking out exemplary programs, working out criteria for selecting teaching candidates, offering opportunities for professional development, teacher induction and support, collaboration, and more importantly, developing reliable tools providing evidence of gains in teachers’ performance.
Teacher effectiveness factors in the USA
http://znp.udpu.edu.ua/issue/view/11534
Keywords: ефективність педагогічної діяльності; якість викладання; педагогічна освіта; характеристики вчителя; педагогічний стаж; оптимізація підготовки вчителів; оцінювання ефективності; США